(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2019)
The aim of this study was to investigate whether fruit juices available in markets of Bangladesh contain any preservative. A specific RP-HPLC method was developed, validated and applied to identify and quantify preservatives including benzoic acid, sorbic acid, methyl paraben and propyl paraben simultaneously in 50 different products. These additives were separated by C18 column in mobile phase composed of methanol and acetate buffer (pH 4.4) in the ratio of 50:50 with a flow rate of 0.7 mL/min, and detected at 254 nm. Linearities for benzoic acid, sorbic acid, methyl paraben and propyl paraben were determined in the range of 20-170 ppm (r2 0.997), 12-42 ppm (r2 0.994), 10-60 ppm (r2 0.993) and 10-60 ppm (r2 0.992) respectively. Limit of detection (LOD) and limit of quantification (LOQ) were 5.46 ppm and 16.5 ppm for benzoic acid while for sorbic acid they were 1.08 ppm and 3.30 ppm, respectively. Benzoic acid was detected in a range of 96.1 to 441 ppm in 9 fruit juices while in 7 fruit juices sorbic acid was found in a range of 105 - 444 ppm. The values were within the maximum allowable ranges for fruit juice (1000 ppm for both benzoic acid and sorbic acid) as suggested by the Joint FAO/WHO Expert Committee on Food Additives (JECFA). None of the juice product was found to contain methyl paraben or propyl paraben Dhaka Univ. J. Pharm. Sci. 18(2): 195-208, 2019 (December)